Peningkatan Performance Arang Aktif Sabut Buah Pinang (Areca Catechu L) sebagai Adsorben Kation - Maria Novia Luruk Atok; I Wayan Budiarsa Suyasa; James Sibaran (Syntax Corporation Indonesia, 2024)
This study aims to see the effect of carbonization temperature on areca coir charcoal, the effect of activator H3PO4 on acidity and surface area, optimal pH and adsorption contact time, effective alarm and active adsorption of areca nut activated charcoal. Areca nut coir charcoal carbonized at various temperatures to determine its optimum carbonization temperature, then activated with H3PO4 at concentrations of 0.5M, 1M and 2M to adsorb Cu (II) metal ion. The results of this study indicate that the effect of areca nut charcoal obtained at each carbonization temperature (3000C, 4000C, 5000C and 6000C) is quite good, but the optimum carbonization temperature is 5000C with reference to the quality standard according to SNI 06-3730-1995. The surface acidity values ​​of activated areca nut coir H3PO4 0.5M, 1M and 2M were 5.43 mmol/g, 5.78 mmol/g and 8.35 mmol/g, respectively. The surface area of ​​H3PO4 activated charcoal with concentrations of 0.5M, 1M and 2M analyzed using the BET test showed values ​​of 0.00 m2/g, 21.273 m2/g and 75.101m2/g, respectively. The optimum pH is pH 7 and the optimum contact time is 60 minutes. The adsorption ability of the activated charcoal is very high so it is very good to be used to adsorb metal ions.